Els Fragments del Sacramentari de Sant Boi de Lluçanès (Vic. Bib. Espisc., Frag I/6) - Gros i Pujol, Miquel dels Sants (Miscel·lània litúrgica catalana, 2005)
The seventeen folios of the Vic, Episc. Lib., Frag. I/6 manuscript are the remains of a mixed Gregorian sacramentary from the parish of Sant Boi de Lluçanès. They were written in the last quarter of the 10th century, several changes having been introduced in the second quarter of the 12th century, thus adapting its canon to the standards of that time, which is what makes it such a singular piece.